Understanding Home in the Chinese Cultural Context: Insights From Postnatal Women's 'Doing the Month'. (22nd April 2021) - Lin, Yuancheng; Wang, Min; Chen, Xiaoxin; Chen, Canwen
Abstract: We use several research tools, such as observations, interviews and textual analysis, to assess the experience of 'doing the month' in Yuezi Clubs with the aim of deepening understanding of the Chinese 'home'. Analysis of data from three Yuezi Clubs in Guangzhou reveals that the traditional 'doing the month' exacerbates intergenerational and regional customary conflicts in modern Chinese families. However, the emergence of the Yuezi Club was a timely invention that has averted such conflicts. We find that Yuezi Clubs strengthen nuclear family bonds. This paper extends the role of capital in shaping the Chinese home, including the social construction. Our findings uncover specific cultural practices in Chinese homes and expand Marxist theory in furthering understanding of Chinese homes. Abstract : This paper examines the particularity of Chinese customs for understanding home, and investigates how the postnatal Chinese women's experience of 'doing the month' contributes to the understanding of home. We find that 'doing the month' has intensified the intergenerational and regional conflicts in modern Chinese family. The health market has founded a buffer zone by which the family tensions could be largely resolved. And it also strengthens the relationship ties of the nuclear family. This paper also extends capital as a new dimension to understand home, linking consumptions to the construction of the social status as well as the development of a family.